Analisis Pengendalian Kualitas Produk Pentol Cilok Menggunakan Metode Statistical Process Control di Kabupaten Sidoarjo (Studi Kasus Pada UMKM Pentol Cilok Mitra Kabupaten Sidoarjo) - Gizzeo Ogjha Bimma Subekti; Rahmat Dhandy; Septine Brillyantina; Julia Agustina (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Quality control is an essential aspect of food production to ensure product consistency, minimize defects, and improve customer satisfaction. However, many Micro, Small, and Medium Enterprises (MSMEs) still experience quality variations due to the absence of systematic quality control practices. This study aimed to analyze the quality control process of Pentol Cilok Mitra MSME in Sidoarjo Regency using the Statistical Process Control (SPC) method, identify the dominant types and causes of product defects, and formulate improvement recommendations. This research employed a quantitative descriptive approach. Data were collected through observation, interviews, documentation, and check sheets during 20 production observations with 400 samples in each observation, resulting in a total of 8,000 observed products. The data were analyzed using SPC tools, including check sheets, p-control charts, Pareto diagrams, process capability analysis, and Ishikawa diagrams. The results showed that 998 products (12.48%) were defective. The dominant defects consisted of non-uniform shape (42%), texture defects (26%), inappropriate product temperature (21%), and non-uniform color (11%). The p-control chart indicated that the production process was generally under statistical control, although several observations of shape defects approached the upper control limit. The Ishikawa analysis revealed that defects were mainly caused by human, material, equipment, method, and environmental factors. The study recommends implementing standard operating procedures, standardizing raw materials, improving production equipment, conducting routine quality inspections, and enhancing workplace conditions to improve process consistency and product quality.